2022
DOI: 10.1111/cid.13140
|View full text |Cite
|
Sign up to set email alerts
|

Changes in implant stability using different site preparation techniques: Osseodensification drills versus piezoelectric surgery. A multi‐center prospective randomized controlled clinical trial

Abstract: Introduction Implant stability is influenced by bone density, implant design, and site preparation characteristics. Piezoelectric implant site preparation (PISP) has been demonstrated to improve secondary stability compared with conventional drilling techniques. Osseodensification drills (OD) have been recently introduced to enhance both bone density and implant secondary stability. The objective of the present multi‐center prospective randomized controlled trial was to monitor implant stability changes over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The dental implants of the present study were inserted into preparations made using conventional drilling techniques. A recent study [ 42 ] demonstrated that other good alternatives, for posterior regions of the maxilla, such as piezoelectric tips or with osseodensification drills also presents excellent implant stability quotients and survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…The dental implants of the present study were inserted into preparations made using conventional drilling techniques. A recent study [ 42 ] demonstrated that other good alternatives, for posterior regions of the maxilla, such as piezoelectric tips or with osseodensification drills also presents excellent implant stability quotients and survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…This protocol is particularly effective in soft bone where the implant bed is intentionally under-prepared, resulting in improved PS [14]. Alternatively, other surgical techniques have been suggested to enhance the density of the bone surrounding the implant, such as manual bone compaction, osseodensification using burs, or utilizing piezoelectric preparation [15]. Recently, several authors have explored the use of magnetodynamic technology in implant rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Success depends on many factors. Not only the dental implant but also the preparation of the implant bed represent significant factors for success [1].…”
Section: Introductionmentioning
confidence: 99%